Sustainable Livelihood and Vulnerability Context: Evidence from Mainland and Coastal Villages - Yunisvita; Muhyiddin, Nurlina T; Hamira; Andaiyani, Sri (Jurnal Ekonomi Pembangunan, 2025)
This study offers an empirical assessment of the sustainable livelihood components among rural households in South Sumatra, contributing original insights into how different livelihood capitals interact with household well-being. The research aims to analyze the vulnerability context, evaluate the sustainability level of various livelihood assets, and examine the relationship between livelihood capitals and outcomes. Using a quantitative approach within the sustainable livelihood framework, data were collected from households in two villages: mainland and coastal areas. The findings indicate that the overall livelihood sustainability of rural households in both locations falls within the medium category. Physical and natural capitals were the most dominant assets, while financial capital was at a moderate level, and social and human capitals were considerably underdeveloped. The low levels of education among respondents were closely linked to the limited accumulation of human and social capital. Further analysis revealed that certain livelihood assets, particularly social and natural capital, had a significant association with household health status, reflecting a tangible impact on livelihood outcomes. These findings underscore the need for targeted policy interventions that prioritize human capital development and community-based social strengthening to enhance overall livelihood sustainability in rural areas.